2005
DOI: 10.1039/b415057k
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, structural analyses and redox kinetics of four-coordinate [CuL2]2+and five-coordinate [CuL2(solvent)]2+complexes (L = 6,6′-dimethyl-2,2′-bipyridine or 2,9-dimethyl-1,10-phenanthroline): completely gated reduction reaction of [Cu(dmp)2]2+in nitromethane

Abstract: [Cu(2,9-dimethyl-1,10-phenanthroline)(2)](2+) and [Cu(6,6'-dimethyl-2,2'-bipyridine)(2)](2+/+) complexes with no coordinated solvent molecule were synthesized and the crystal structures were analyzed: the coordination geometry around the Cu(i) center was in the D(2d) symmetry while a D(2) structure was observed for the four-coordinate Cu(ii) complexes. Coordination of a water or an acetonitrile molecule was found in the trigonal plane of the five-coordinate Cu(ii) complex in the Tbp(trigonal bipyramidal) struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 53 publications
4
61
1
Order By: Relevance
“…[19] Thep roton likely bond to the open copper sites to afford copper hydride species for the release of hydrogen. [19] Thep roton likely bond to the open copper sites to afford copper hydride species for the release of hydrogen.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[19] Thep roton likely bond to the open copper sites to afford copper hydride species for the release of hydrogen. [19] Thep roton likely bond to the open copper sites to afford copper hydride species for the release of hydrogen.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In general, metal complexes of 2,2 0 -bipyridine (bpy) (and its derivatives) continue to be of great interest in many areas of chemistry, owing to their interesting structural, spectroscopic, catalytic, biomimetic, as well as photophysical and photochemical properties [13][14][15][16][17]. Pb(II) complexes with 2,2 0 -bipyridine and 4,4 0 -bipyridine ligands [18][19][20] were subject to frequent studies.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14] On the other hand, we found that the electron transfer (cross) reactions between different copper complexes and the electron self-exchange reactions are not gated. Single crystal analyses revealed that [Cu(pdt) 2 (H 2 O) 2 ](BF 4 ) 2 was in the D 2h symmetry with two axial water molecules and two symmetrically coordinated equatorial pdt ligands, while the coordination structure of [Cu(pdt) 2 ]BF 4 was a squashed tetrahedron (dihedral angle = 54.87 o ) with an asymmetric coordination by two pdt ligands: one pdt ligand coordinated to Cu(I) through pyridine-N and triazine-N2 while another pdt through pyridine-N and triazine-N4, and a stacking interaction between the phenyl ring on one pdt and the triazine ring on another pdt caused the squashed structure and nonequivalent Cu-N bond lengths.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14] On the other hand, we found that the electron transfer (cross) reactions between different copper complexes and the electron self-exchange reactions are not gated. the structural change (inner-sphere reorganization) is the essential factor that induces gated phenomena.…”
mentioning
confidence: 99%